2011
DOI: 10.1007/s10571-011-9672-7
|View full text |Cite
|
Sign up to set email alerts
|

Regional Changes in Gene Expression after Limbic Kindling

Abstract: Repeated electrical stimulation results in development of seizures and a permanent increase in seizure susceptibility (kindling). The permanence of kindling suggests that chronic changes in gene expression are involved. Kindling at different sites produces specific effects on interictal behaviors such as spatial cognition and anxiety, suggesting that causal changes in gene expression might be restricted to the stimulated site. We employed focused microarray analysis to characterize changes in gene expression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…These findings were in line with previous studies that memory impairments could be observed less than 3-4 weeks after the final kindling stimulation in animals with generalized seizures (Lopes da Silva et al, 1986;Feasey-Truger et al, 1993;Gilbert et al, 2000). Similar to our results, no changes in the gene expression level of GABA A (Kamphuis et al, 1995b;Nishimura et al, 2005) and NMDA (Kamphuis et al, 1995a;Corcoran et al, 2011) receptor subunits have been reported at 2-4 weeks following the last kindling stimulation.…”
Section: Discussionsupporting
confidence: 94%
“…These findings were in line with previous studies that memory impairments could be observed less than 3-4 weeks after the final kindling stimulation in animals with generalized seizures (Lopes da Silva et al, 1986;Feasey-Truger et al, 1993;Gilbert et al, 2000). Similar to our results, no changes in the gene expression level of GABA A (Kamphuis et al, 1995b;Nishimura et al, 2005) and NMDA (Kamphuis et al, 1995a;Corcoran et al, 2011) receptor subunits have been reported at 2-4 weeks following the last kindling stimulation.…”
Section: Discussionsupporting
confidence: 94%
“…Male Sprague-Dawley rats (at 35 postnatal days, p35) were anesthetized and subjected to stereotactic surgery for electrode implantation (Greenwood et al, 1991 ; Corcoran et al, 2011 ). Five electrodes were implanted: one in the right basolateral amygdala complex for stimulation and recording; and two bilaterally implanted pairs for recording in the primary motor (Br.…”
Section: Methodsmentioning
confidence: 99%
“…The surgical procedures for electrode implantation were carried out as described (Greenwood et al, 1991; Corcoran et al, 2011), with minor modifications. The skull was leveled and a teflon insulated bipolar stimulating and recording electrode of twisted stainless steel (0.2 mm of outer diameter, Plastics One Inc.) implanted in the right BLA to deliver kindling stimulation and record the ADs after the stimulus ended.…”
Section: Methodsmentioning
confidence: 99%